The bio-theo-political paradigm of autarchy and the paradoxical living God - Grassi, Martín (2021)
In the Western tradition, life has been defined within the idea of reflexivity and unity. These two features of life are intertwined in what I call the Bio-Theo-Political Paradigm of autarchy, in which living beings are defined primarily as self-sufficient entities. The perfect living being, thus, will be the most autarchic, one that can achieve perfect unity within its own self- referred dynamics. This perfect living being is God, and Western theology (both Greek and Christian) conceptualized God as “thought of thought”, for only the intellect can achieve a pure reflexive unity. However, Plotinus and Jean-Paul Sartre (two very different philosophers, coming from very different traditions and in very different contexts) showed the difficulties of such a definition of God. This paper aims at problematizing the Bio-Theo-Political Paradigm of autarchy by showing its inconsistency when reaching the idea of a perfect living being. In doing so, a need to rethink life and God is fostered, a need that Christian Theology in particular should face in order to build a theology of a Trinitarian living God.